ANALISIS PENGARUH ATRIBUT PRODUK DAN PROMOSI TERHADAP PERSEPSI KUALITAS MOTOR MEREK MILLENIUM (PRODUK MOTOR CINA) - Waidi, Drajat Adhitya; S, Purbayu Budi (JURNAL BISNIS STRATEGI, 2001)
Wrong custumer perception of a product can cause negative effect for it’s marketing, more over if that product is new product that trying to enter in market that has already been occupied by other product which have been already known cy costumer. If this situation continuos happens will affect the image of product it self, of course it is important to improve the perception toward the product so costumer perception becomes positive and finally will affect buying intention of costumer.                This research analyze the costumer perception on motor cycle product called Millenium which is produce in China, after the selected costumer assessing directly by following promotion campaign such as exhibition and test drive. Attributes, that are investigated, are costumer assesment on extrinsic attributess, promotion strategy toward quality perception that cause buying intention.